Ramsar Lakes in the Foothills of Himalaya, Pokhara- Lekhnath, Nepal: an overview - Paudel, Namita; Adhikari, Subash; Paudel, Ganesh (Janapriya Journal of Interdisciplinary Studies, 2018)
Wetlands are the most dynamic ecological units on the earth delivering voluminous ecosystem services. Pokhara-Lekhnath has prosperous wetland ecosystems with nine lake clusters nominated as 10th Ramsar site of Nepal in 2016 that act as diverse and, distinctive biodiversity hot spot and habitat. These wetlands afford abundant ecosystem services and assist vulnerable, endangered and critically endangered species. However these lakes are under tremendous pressure due to rapid urbanization, natural erosion, encroachments, land use changes in the catchment and anthropogenic inputs resulting in the shrinkage of area and deteriorationin the hydrological, economic and ecological characteristics. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), page: 134-147